Efektivitas Arang Cangkang Kopi dalam Penurunan Kadar Besi (Fe) pada Air Sumur - Meika Wafiq Wikansari; Wulandari Meikawati; Shalihat Afifah Dhaningtyas; Mifbakhuddin, Mifbakhuddin (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Well water is one of the main water sources to meet the needs of the community, especially in rural areas. However, the quality of well water often does not meet health standards because it contains heavy metals such as iron (Fe). Therefore, a simple and environmentally friendly alternative technology is needed that can be utilized by the community. One method used is filtration using natural adsorbent media, one of which is coffee shell charcoal. This study aims to determine the effectiveness of coffee shell charcoal in reducing Fe levels in well water. The research design used was a true-experimental with a one-group pre-test and post-test. Well water samples were tested for Fe levels before and after filtration using coffee shell charcoal with varying media thicknesses (40, 50 & 60 cm) and contact times (30, 45 & 60 minutes). Laboratory analysis was carried out using the Atomic Absorption Spectrophotometry (AAS) method. The results showed that the average percentage of Fe reduction reached 75,36%. Media thickness and contact time significantly affected the effectiveness of Fe reduction with p values ​​of 0,03 and 0,01, respectively (p < 0,05). A medium with a thickness of 60 cm and a contact time of 60 minutes provided the most optimal results, with final Fe levels below the threshold set by Minister of Health Regulation No. 32 of 2017 (≤ 1 mg/L). In conclusion, coffee husk charcoal has proven effective as a simple filtration medium for reducing Fe levels in well water.